RETROSPECTIVE ANALYSIS OF FATAL RAILWAY CASES IN PRAYAGRAJ - A THREE YEAR AUTOPSY BASED STUDY (Journal of Forensic Medicine & Toxicology, 2025)
The present study retrospectively examined all railway-related deaths brought for medicolegal autopsies using hospital records from 1st Jan 2021-31st Dec 2023 at Swaroop Rani Nehru Hospital, Moti Lal Nehru Medical College, Prayagraj, U.P. There were a total of 297 registered cases of railway fatalities during the study period, of which 243 cases had complete data and were included in the study. The information about the deceased was gathered using a proforma created especially for the purposes of this study. The studies showed most of the victims were between 21 to 30 years 89(36.62%). Among the total of 243 studied cases, 185(76.13%) were males. In most cases, the incident occurred while crossing Railway track 95 (39.09%). There were 153 victims (62.96%) from rural areas, while the remaining victims were from urban areas 90(37.04%). Students accounted for 74 (30.45%) of railway-related fatalities, followed by self-employed individuals 66 (27.16%). Accidental manner was the most common 165 (67.90%). Implementing stringent traffic laws and raising public knowledge of safety precautions can help lessen the impact of these avoidable deaths.
Keywords: Railway; Fatalities; Injuries; Traffic Laws